UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH DAN KEMAMPUAN BERPIKIR KREATIF MATEMATIKA DENGAN MENGGUNAKAN PENDEKATAN OPEN ENDED PADA SISWA DI KELAS VIII SMP MUHAMMADIYAH 02 MEDAN TAHUN AJARAN 2015/2016 - Roida Nasution; Siti Halimah (Universitas Islam Negeri Sumatera Utara Medan, 2016)
Efforts to Improve Problem Solving Ability and Creative ThinkingSkills Mathematical Approach Using Open Ended At Students In ClassVIII SMP Muhammadiyah 02 Terrain Academic Year 2015/2016.Thesis, Department of Mathematics Education and Teaching FacultyTarbiyah State Islamic University of North Sumatra, Medan, 2016. Thisstudy aims to determine: 1) The ability of solving students 'problemsbefore using the approach of open-ended, 2) Ability solving students'problems after using the approach of open-ended, 3) Ability to thinkcreatively math student before using the approach of open-ended, 4)Ability to think creative math students after using the open-endedapproach, 5) Description of the application process is open-endedapproach, 6) Description of student response during the learningprocess with the adoption of open-ended approach. This research is aclassroom action research (PTK) is conducted in two cycles, each cycleconsisting of two meetings. The instrument used to collect the dataconsists of the initial capability test, post test I, II post test, interviewand observation sheet. The research findings inform, before theadoption of the open-ended approach to the problem solving andcreative thinking abilities mathematics of the 32 students who took thetests beginning no complete student in achieving the KKM. Onceapplied the open-ended approach to the students in class VIII-B proveneffective and can improve the ability of students. This can be seen in thefirst cycle was obtained by 15 students who completed reaching theKKM, while 17 students have not fully reached the KKM. In the secondcycle test was obtained by 28 students and 4 students said to completethe unfinished reached the KKM. In the open-ended approach to theimplementation of the first cycle teachers have difficulties in timemanagement is less effective and efficient. But in the second cycle isdone then the teachers are increasingly skilled at managing time byutilizing pembelajan media actively. And the result of studentsachieving an average value classical. The response of students in the process of implementing an open-ended approach to increased activitywhere students in the first cycle by either category. Then in the secondcycle students learning activities increased with very good category. Itcan be seen that the students responded well and active in learningmathematics with application of the open-ended approach.